Army recruits of Indian origin: early detection and further prevention of noise induced hearing loss by otoacoustic emission - Joshi, Himanshu; Das, Avinash (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: There has been no study on Indian population which has tested ears prone for “noise induced hearing loss”. Also, no study on recruits of Indian origin could be found in the literature, so an attempt has been made to screen the individuals to prevent noise induced hearing loss. Methods: Otoacoustic emission (OAE) screening is done over recruits before and after first exposure to loud noise of rifle firing in our study. Recruits were followed up at 04 hours, 24 hours, 01 month and 06 months after exposure. Individuals showing variation in OAE at 24 hours were also subjected to pure tone audiometry (PTA) at 01 month and 06 months. Results: 98 recruits developed ‘refer’ in OAE at initial 4 hours out of which 67 recruits recovered in 24 hours. Remaining 31 recruits (45 ears) when followed up and screened at 01 month shows ‘refer’ in OAE in 22 recruits (37 ears) and high frequency loss on PTA in 17 recruits (31 ears). At 06 months 16 recruits (28 ears) shows ‘refer’ in OAE and 12 recruits (22 ears) shows dip in high frequency in PTA. Conclusions: OAE is more sensitive tool for early detection of noise induced hearing loss. This study also correlates time and frequency involved in OAE in detecting early hearing loss as the individuals who show refer in OAE at both 04 hours and 24 hours with both 3 kHz and 4 kHz involved are more prone for noise induced hearing loss in future.